9 - Secondary Education - A ’Tool’ for National Development in Ghana. A Critical Appraisal of the Post-Colonial Context: 10.4314/ad.v28i2.22182 - Quist Hubert Ο. (Africa Development, 2003)
The paper appraises the role of secondary education as a 'tool' for national development in post-colonial Ghana. In so doing, it analyses the problems of secondary education provision focusing on funding and reform. I have argued that - notwithstanding the World Bank's present support for universal primary education throughout Africa, a project commenced in Ghana as early as 1951, which represents a major shift from the Bank's previous endorsement ( 1960s) of university education as the panacea to Africa's development challenges - secondary education remains vital to Ghana's development aspirations. As the most accessible form of higher education in Ghana today, increased attention to, and expansion of secondary education has a greater potential than primary edu cation of sustaining literacy levels attained, raising political awareness and thus advancing democracy, as well as supplying sufficient middle-level manpower crucial to national development. Hubert Ο. Quist, Department of Educational Foundations, University of Cape Coast, Ghana.